Análise biomecânica, morfológica e da resposta nociceptiva em modelo animal de Mucopolissacaridose tipo I - Ferreira, Nicole Yolanda [UNIFESP] (2019)
Mucopolysaccharidoses (MPS) are a group of inborn errors of metabolism (IEM), in which specific lysosomal enzymes that participate of glycosaminoglycan (GAG) degradation are deficient or inactive. Musculoskeletal impairment is an important component of the morbidity related to the disease, once it causes a major impact in patients’ health and life quality. Characteristics such as decreased enzyme activity and lysosomal storage in different types of cells are observed in MPS I murine models, making them an important and reliable tool for better understanding the pathogenic mechanisms of the disease. Despite all existing evidence regarding musculoskeletal alterations in MPS I, it is still unclear how these influence bone matrix quality and its biomechanical properties. Objective: Evaluate the nociceptive response to heat in 3 and 6-month old wild type (Idua +/+) and MPS I knockout mice (Idua -/-), as well as bone matrix morphological, biomechanical, and histological properties. Method: Nociceptive response to heat from 3 and 6-month old wild type (Idua +/+) and MPS I knockout mice (Idua -/-) was evaluated. In addition, morphological, biomechanical, and histological analysis of femurs from the same group of animals were perfomed. Results and conclusions: No difference was observed in the nociceptive response to heat for all animal groups ang ages. Femurs from 3-month old Idua -/- mice were found to be smaller and less resistant to fracture when compared to their age matched controls. Also, at this age, femurs from 3-month old Idua - /- mice presented important alterations in articular cartilage, trabecular bone architecture, and collagen types I and III deposition. At 6 months of age, femurs from Idua -/- mice were more resistant to fracture than those from Idua +/+. Our results suggest that the clear abnormalities observed in bone matrix and articular cartilage in 3-month old Idua -/- animals caused bone tissue to be less flexible and more likely to fracture, whereas in 6-month old Idua -/- group the ability to withstand more load before fracturing than wild type animals might suggest that at this age bones become more resistant than at 3 months of age.